NURTURING CIVIC COMPETENCE OF UNIVERSITY STUDENTS THROUGH SCOUTING EDUCATION AS STRENGTHENING YOUNG GENERATION CHARACTER AT MUHAMMADIYAH UNIVERSITY OF SURAKARTA - Sapriya, Beny Dwi Lukitoaji (Jurnal Civicus, 2015)
The purpose of this study was to reveal the patterns of the civic competence of the university students where Scouting Education was attempted as strengthening character in young at the Civic Education Department of FKIP UMS. This research showed several finding, namely: (1) Knowledge was built by hidden. However, skills were nurtured through principle of ‘learning by doing’ within teamworks, while, characters were nurured by instilling the values of tri satya and dasa dharma through habituation and coaching. (2) Constraints in nurturing civic competence are the univesrsity students’ shyness, lack of responsibility, and late arrivals. Solutions were the teachers’ firmness, and ‘reward and punishment’ in the learning process. (3) Nurturing students’ civic competence through Scouting Education has resulted in a more discipline attitude as well as more developed spiritual, social, and personal competences, and skills.Keywords: Nurturing Civic Competence, Education Scouting, Young Generation Character.